2007
DOI: 10.1093/hmg/ddm188
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Flnb gene in mice phenocopies the human disease spondylocarpotarsal synostosis syndrome

Abstract: Spondylocarpotarsal synostosis syndrome (SCT) is an autosomal recessive disease that is characterized by short stature, and fusions of the vertebrae and carpal and tarsal bones. SCT results from homozygosity or compound heterozygosity for nonsense mutations in FLNB. FLNB encodes filamin B, a multifunctional cytoplasmic protein that plays a critical role in skeletal development. Protein extracts derived from cells of SCT patients with nonsense mutations in FLNB did not contain filamin B, demonstrating that SCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 15 publications
7
69
0
Order By: Relevance
“…This finding is interesting as Flnb knockout mice show impaired development of the microvasculature and skeletal system with bone and joint fusions [18,19]. This also suggests a link between A-to-I editing of the Flnb transcript and the main function of the encoded protein.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding is interesting as Flnb knockout mice show impaired development of the microvasculature and skeletal system with bone and joint fusions [18,19]. This also suggests a link between A-to-I editing of the Flnb transcript and the main function of the encoded protein.…”
Section: Discussionmentioning
confidence: 96%
“…MIM Number: *300017 and *603381, respectively). This difference is mirrored in the mouse, where the deletion of the Flna gene causes lethal heart and vascular defects [16,17] while the deletion of the Flnb gene leads to lethal skeletal malformations with bone fusions [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…The gene FLNB in the first region (locus: Chr 3: 57918877-58055004) encodes filamin B, a multifunctional cytoplasmic protein that plays a critical role in skeletal development. Flnb knockout mice are phenotypically similar to individuals with spondylocarpotarsal syndrome as they exhibited short stature and similar skeletal abnormalities (Farrington-Rock et al 2008). FLNB is known to be associated with height in African Pygmies (Jarvis et al 2012;Lachance et al 2012) and has also been reported to be associated with osteoporosis in women (Wilson et al 2009).…”
Section: Demography and Selection In African Pygmiesmentioning
confidence: 98%
“…High levels of filamin A and filamin B have previously been detected in vessels (15)(16)(17) and in endothelial cells in culture (17)(18)(19). Knock-out experiments show the functional importance of each isoform: filamin A knock-out mice die during development due to aberrant vascular patterning and cardiac defects (20,21), whereas filamin B deficiency in mice mainly causes skeletal malformations (22)(23)(24) and vascular deficiencies (23).…”
mentioning
confidence: 99%